2000
DOI: 10.1021/bi992495e
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Membrane Assembly of a Transmembrane Region from Neu

Abstract: Transmembrane domains of receptor tyrosine kinases are increasingly seen as key modulatory elements in signaling pathways. The present work addresses problems surrounding expression, isolation, secondary structure recovery, and assembly into membranes, of the relatively large quantities of transmembrane peptides needed to investigate these pathways by NMR spectroscopy. We demonstrate significant correspondence between SDS-PAGE behavior of such peptides and their (2)H NMR spectra in lipid bilayer membranes. A 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 37 publications
6
39
0
Order By: Relevance
“…42 Furthermore, it has been reported that a peptide corresponding to the TM of the EGF receptor (erbB1) migrated as a monomer in SDS-PAGE, 54 and isolated erbB2 TM peptides also migrate predominantly as monomers. 55 These results with isolated TM peptides are consistent with the SDS-PAGE analysis of our SN-fusion constructs. Some reports do indicate, however, peptides corresponding to the TM of the proto-oncogenic neu receptor from rats, a homolog of erbB2, migrate as something larger than monomers on SDS-PAGE.…”
Section: Weak Interactions Of the Erbb Tmssupporting
confidence: 88%
See 1 more Smart Citation
“…42 Furthermore, it has been reported that a peptide corresponding to the TM of the EGF receptor (erbB1) migrated as a monomer in SDS-PAGE, 54 and isolated erbB2 TM peptides also migrate predominantly as monomers. 55 These results with isolated TM peptides are consistent with the SDS-PAGE analysis of our SN-fusion constructs. Some reports do indicate, however, peptides corresponding to the TM of the proto-oncogenic neu receptor from rats, a homolog of erbB2, migrate as something larger than monomers on SDS-PAGE.…”
Section: Weak Interactions Of the Erbb Tmssupporting
confidence: 88%
“…Some reports do indicate, however, peptides corresponding to the TM of the proto-oncogenic neu receptor from rats, a homolog of erbB2, migrate as something larger than monomers on SDS-PAGE. 36,55,56 While specific protein-protein interactions determined by the amino acid sequence are important for TM helix interactions, the environment can also be a critical factor in the investigation of membrane proteins. Successful solution studies can depend on the choice of an appropriate detergent.…”
Section: Weak Interactions Of the Erbb Tmsmentioning
confidence: 99%
“…5a). Reduced electrophoretic mobility has been observed previously for various proteins (27)(28)(29)(30)(31)(32), and this can stem from unusual amino acid composition, intrinsic net charge or protein oligomerization. The pI values of SRC proteins are 5.98, 5.02, and 4.61 for SRC4, 8, and 12, respectively.…”
Section: Construction Of Recombinant Expression Plasmid Pet21a(ϩ)-srcn-mentioning
confidence: 59%
“…The cleaved sample was dialyzed extensively at 4°C against water, and the turbid solution was lyophilized. The lyophilized proteins were solubilized by using a mixture of a formic acid-acetic acid-chloroform-trifluoroethanol (FACT) mix (21), acetonitrile, and water in a ratio of 1:3:3 and purified by preparative RP-HPLC as described (22). The purified TM-CYTO protein was lyophilized and stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%